Frequency-Tagging Electroencephalography of Superimposed Social and Non-Social Visual Stimulation Streams Reveals Reduced Saliency of Faces in Autism Spectrum Disorder - Vettori, Sofie; Dzhelyova, Milena; Van der Donck, Stephanie; Jacques, Corentin; Steyaert, Jean; Rossion, Bruno; Boets, Bart (Frontiers in Psychiatry, 2020)
Individuals with autism spectrum disorder (ASD) have difficulties with social communication and interaction. The social motivation hypothesis states that a reduced interest in social stimuli may partly underlie these difficulties. Thus far, however, it has been challenging to quantify individual differences in social orientation and interest, and to pinpoint the neural underpinnings of it. In this study, we tested the neural sensitivity for social versus non-social information in 21 boys with ASD (8-12 years old) and 21 typically developing (TD) control boys, matched for age and IQ, while children were engaged in an orthogonal task. We recorded electroencephalography (EEG) during fast periodic visual stimulation of social versus non-social stimuli to obtain a direct, fast and implicit neural measure of the relative social bias. Streams of variable images of faces and houses were superimposed, and each stream of stimuli was tagged with a particular presentation rate (i.e. 6 Hz and 7.5 Hz or vice versa). This frequency-tagging method allows disentangling the respective neural responses evoked by the different streams of stimuli. Moreover, by using superimposed stimuli, we controlled for possible effects of preferential looking, spatial attention and disengagement. Based on four trials of 60 seconds, we observed a significant three-way interaction. In the control group, the frequency-tagged neural responses to faces were larger than those to houses, especially in lateral occipito-temporal channels, while the responses to houses were larger over medial occipital channels. In the ASD group, however, faces and houses did not elicit significantly different neural responses in any of the regions. These results confirm that the brain of TD boys is tuned towards social stimuli. Boys with ASD, however, are less neurally tuned towards social stimuli, possibly impacting daily-life social communication and interaction. We conclude that frequency-tagging EEG provides a fast, objective and reliable neural measure of decreased social bias in ASD.